Renewable energy and current account balance nexus - Bildirici, Melike; Kayikci, Fazil (SPRINGER HEIDELBERG, 2022)
Renewable energy is in the center for providing a sustainable energy future. Renewables are the key for overcoming the energy problems. This paper investigated the dynamic and causal relationship among renewable energy production, current account balance, energy imports, renewable energy consumption, and economic growth in the 1976-2019 period for G20 countries through panel Fourier bootstrapping ARDL model. According to empirical results, the evidence of cointegration between the selected variables was determined. Results indicate that economic growth, energy imports, energy consumption, and current account balance provide the important impacts on renewable energy generations. Our results determined that there is a unidirectional causality from energy imports, renewable energy consumption, and current deficit to renewable energy production. As countries decrease their dependence on the imports of energy, this may both increase the quality of environment through production of more renewable energy and reduce current account imbalances.
Keywords: Renewable energy; Current account balance; ECONOMIC-GROWTH NEXUS; OIL PRICE SHOCKS; PANEL-DATA; CONSUMPTION; TRADE; COINTEGRATION; CAUSALITY; COUNTRIES; DYNAMICS; INDUSTRY; Environmental Sciences & Ecology